Inter-Institutional Articulation Model Focused on Aligning Professional Profiles Expected by the Business Sector - Díaz Cañas, Edith Johanna
An inter-institutional articulation model is proposed, with an emphasis on innovation, which promotes the match between the profiles of university graduates of administrative career programs and the professional expectations in the business sector. This research was carried out through documentary and field information sources, combined with the review of databases, indices of job offers in Colombia, placement of professionals according to academic level and the relationship between recent graduates and their entry into the labour market. Semi-structured interviews, mapping of job expectations and graduate profiles and trend analysis were used. Based on this research, the approach of the programs of Administrative, Economic and Financial Sciences of the Colombian Higher Education Institutions (HEI) to the model proposed in this research was identified.